Spatial analysis of the late Middle Palaeolithic open-air site of Bout-des-Vergnes (Bergerac, Dordogne) based on lithic technology and refitting. (August 2020) - Courbin, Paul; Brenet, Michel; Michel, Alexandre; Gravina, Brad
Highlights: Refitting provides a fuller understanding of the spatial organisation of open-air sites. Discoidal debitage found across the site is contemporaneous with imported scrapers on Levallois blanks and bifaces. Differences between technological components of the assemblage reflect the function and use-lives of tools. Abstract: The late Mousterian open-air site of Bout-des-Verges was the subject of large-scale rescue excavations between 2012 and 2103 that yielded evidence for the spatial organisation of particular techno-typological elements amongst the 900 lithics recovered from the site. Three knapping concentrations in the southwest sector of the site produced two-thirds of the overall lithic assemblage, the remaining pieces were found scattered across the excavated area. Our techno-economic analysis of the Bout-des-Verges assemblage revealed clear differences in terms of raw material economy and artefact transport patterns between the dominant discoidal component and the larger, imported bifaces and Levallois flakes. Refitted reduction sequences and our spatial analysis confirm the three lithic concentrations to be contemporaneous and, by extension, to form part of a single Mousterian occupation with multiple technological components. The majority of discoidal products produced on the site were exported for future use, while the imported bifaces and Levallois scrapers with longer use-lives were transported multiple times by Neanderthal groups.